2016
DOI: 10.13005/bbra/2003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Concurrency of Colchicine and Simvastatin on Variation of Serum Immunoglobulins IgG, IgE, IgM and IgA in Mustard Gas-Wounded Patients

Abstract: Mustard gas as a chemical weapon causes devastating effects on different tissues of the body and there is no perfect antidote against it. This gas is a very strong and nonspecific alkaline agent that is capable of causing inflammation as well as increase of immunoglobulins in the patients. This gas causes irreparable and sever damage to all the body tissues; so finding of effective medicines to treat the mustard gas-exposed patients is of great importance and is the main purpose of this study. This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Many studies had previously shown the anti-in ammatory effect of statin (23,24), but few studies could not demonstrate this effect (25,26). Considering the signi cant reduction in serum cholesterol level in Atorvastatin group it is unlikely that poor adherence to the study protocol could explain the failure to reach statistical difference between groups.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies had previously shown the anti-in ammatory effect of statin (23,24), but few studies could not demonstrate this effect (25,26). Considering the signi cant reduction in serum cholesterol level in Atorvastatin group it is unlikely that poor adherence to the study protocol could explain the failure to reach statistical difference between groups.…”
Section: Discussionmentioning
confidence: 97%
“…In one hand, several studies could show the anti-inflammatory effect of statin [ 26 , 27 ]; however, few could not [ 28 , 29 ]. Considering the significant reduction in serum cholesterol level in the atorvastatin group, it is unlikely that poor adherence to the study protocol was the reason for the failure to reach statistical differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In one hand, several studies could show the anti-in ammatory effect of statin (26,27); however, few could not (28,29). Considering the signi cant reduction in serum cholesterol level in the atorvastatin group, it is unlikely that poor adherence to the study protocol was the reason for the failure to reach statistical differences between groups.…”
Section: Discussionmentioning
confidence: 99%